(untitled) (Bangladesh Journal of Animal Science, 2021)
Growth performance, carcass characteristics and production costs associated with feeding crossbred indigenous chicken on traditional buttermilk coated diets were evaluated. Three batches of day-old Indigenous x Kuroiler crossbred chicks were raised on a commercial diet for one month. At one month, chicken in each of the three batches were weighed and randomly divided into 3 equal groups. Each group comprised of 20 birds. Chicken in each group were either fed coated (dry buttermilk coated maize-bran), combined (buttermilk coated maize bran + commercial diet) or a commercial (control) diet. Average final live weight and feed intake were similar across the three dietary treatments (P>0.05). Feed to gain ratio significantly varied (P<0.05) across dietary treatments with buttermilk coated diets having the highest feed to gain ratio (7.27) compared to combined (4.38) and commercial (3.88) diets. Coated and combined diets yielded similar dressing percentage of 60.2 and 62 compared to 65% obtained with commercial diets. Carcass and organ yield was similar (P>0.05) across dietary treatments. On a 5 point hedonic scale, chicken meat produced using coated diets was more acceptable (2.0), compared to combined (2.1) and commercial (3.1) diets (P<0.05). The highest gross margins accrued from feeding combined and commercial diets. Over-all, results provide evidence of the potential of the combined diet to attain similar growth performance, carcass yield and gross margins as the commercial diet at lower cost. Bang. J. Anim. Sci. 2021. 50 (1):57-63